2009
DOI: 10.1186/1471-2334-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistance in Streptococcus pneumoniae isolates among Spanish middle aged and older adults with community-acquired pneumonia

Abstract: BackgroundPneumococcal diseases remain a major cause of morbidity and mortality worldwide. Updated data on drug-resistance from different populations may be important to recognize changes in disease patterns. This study assessed current levels of penicilin resistance among Streptococcus Pneumoniae causing pneumonia in Spanish middle age and older adults.MethodsAntimicrobial susceptibility was tested for 104 consecutive isolates of Streptococcus pneumoniae recovered from patients 50 years or older with radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
12
3
2
Order By: Relevance
“…In the present study, overall levels of nonsusceptibility to oral benzylpenicillin (13.4%), amoxicillin (2%), cefotaxime (1%), erythromycin (12%), and levofloxacin (0.8%) in S. pneumoniae isolates from elderly patients with pneumonia were lower than the percentages of resistance described in other studies of pneumococcal pneumonia performed in Spain (7,14,30,31). Additionally, and in agreement with recent studies (10,24,31), the trend toward a decrease in nonsusceptible S. pneumoniae isolates seems to be continuing and is associated with a decrease in episodes of pneumonia caused by PCV7 serotypes. PCV7 childhood vaccination in our region seems to have had a beneficial effect in diminishing the (8), none of the isolates causing pneumonia were resistant and only 1% of the isolates obtained during AECOPD episodes showed resistance.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In the present study, overall levels of nonsusceptibility to oral benzylpenicillin (13.4%), amoxicillin (2%), cefotaxime (1%), erythromycin (12%), and levofloxacin (0.8%) in S. pneumoniae isolates from elderly patients with pneumonia were lower than the percentages of resistance described in other studies of pneumococcal pneumonia performed in Spain (7,14,30,31). Additionally, and in agreement with recent studies (10,24,31), the trend toward a decrease in nonsusceptible S. pneumoniae isolates seems to be continuing and is associated with a decrease in episodes of pneumonia caused by PCV7 serotypes. PCV7 childhood vaccination in our region seems to have had a beneficial effect in diminishing the (8), none of the isolates causing pneumonia were resistant and only 1% of the isolates obtained during AECOPD episodes showed resistance.…”
Section: Discussioncontrasting
confidence: 50%
“…In fact, gender, previous antibiotic treatment, and cardiopathy were the only differences between patients with pneumonia with and without COPD. Another two studies performed in Spain found no differences in the antimicrobial resistance of pneumococci causing pneumonia in COPD and non-COPD patients (7,31).…”
Section: Discussionmentioning
confidence: 99%
“…Existing vaccines were even withdrawn from the market. By now, in many parts of the world, the antibiotic resistance of S. pneumoniae bacteria has increased: America [32,33], Africa [34], Europe [35,36], Asia [37][38][39], and Australia [40]. This makes treatment of pneumococcal infections more difficult and stresses the importance of the development of effective vaccines as a strategy to reduce morbidity and mortality caused by S. pneumoniae infection worldwide.…”
Section: Development Of Pneumococcal Vaccinesmentioning
confidence: 99%
“…Previous studies described a tendency for resistant strains to decrease selectively after reduction of antibiotic usage (8,19). PMEN clones have a high genomic plasticity, leading to fast adaption to clinical interventions like capsule switching and evolution of resistance (3).…”
mentioning
confidence: 99%